Optimizing Bilingual Teaching in Developing Students' English Language Skills - Hoerudin, Cecep Wahyu (International Journal of Science and Society, 2024)
Bilingual teaching in Indonesia has great potential in improving students' English skills. However, its implementation faces limited resources, teacher readiness, and support from the school environment and family. By overcoming these challenges, bilingual teaching can have a significant positive impact. This study aims to evaluate the impact of bilingual teaching on the development of students' English skills in Indonesia. This study uses a qualitative approach, collecting data from various relevant sources including research results and previous studies, and analyzing the data systematically. Bilingual teaching significantly improves students' speaking, listening, reading, and writing skills. In addition, this method also increases students' self-confidence and motivation, which ultimately supports their academic success. Government policy support, parental and community participation, and innovation in teaching materials and methods are key factors in the success of bilingual teaching. With commitment from all related parties and continuous efforts, bilingual teaching can be implemented effectively. This is expected to prepare Indonesian students to face global demands in the future.